2017
DOI: 10.1016/j.pscychresns.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hemispherical asymmetry in default-mode functional connectivity and BAIAP2 gene are associated with anger expression in ADHD adults

Abstract: A B S T R A C TAttention deficit hyperactivity disorder (ADHD) is accompanied by resting-state alterations, including abnormal activity, connectivity and asymmetry of the default-mode network (DMN). Concurrently, recent studies suggested a link between ADHD and the presence of polymorphisms within the gene BAIAP2 (i.e., brain-specific angiogenesis inhibitor 1-associated protein 2), known to be differentially expressed in brain hemispheres. The clinical and neuroimaging correlates of this polymorphism are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 82 publications
2
14
0
Order By: Relevance
“…While asymmetries most likely involve the frontoparietal, attention, and default mode networks, no study so far has precisely mapped the exact underlying connectivity asymmetries in full. Studies so far have either focused on asymmetries of connections within the left hemisphere or the right hemisphere (Tzourio-Mazoyer et al 2015 ), address specific regions of interest (Fox et al 2006 ; Xiao et al 2016 ; Hasler et al 2017 ), or have obtained condensed asymmetry metrics by quantifying the mean amount of asymmetric connections per voxel (Joliot et al 2016 ). While these approaches certainly have their merits, they do not provide a full and simultaneously assessment of any connectivity asymmetries between and within hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…While asymmetries most likely involve the frontoparietal, attention, and default mode networks, no study so far has precisely mapped the exact underlying connectivity asymmetries in full. Studies so far have either focused on asymmetries of connections within the left hemisphere or the right hemisphere (Tzourio-Mazoyer et al 2015 ), address specific regions of interest (Fox et al 2006 ; Xiao et al 2016 ; Hasler et al 2017 ), or have obtained condensed asymmetry metrics by quantifying the mean amount of asymmetric connections per voxel (Joliot et al 2016 ). While these approaches certainly have their merits, they do not provide a full and simultaneously assessment of any connectivity asymmetries between and within hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…In ADHD patients, a study demonstrated that higher connectivity between the right hippocampus, the parietal lobe (supramarginal and angular gyrus), and the frontal lobe (superior and middle frontal gyrus) in carriers of the AG or GG variant of rs8079626 within the BAIAP2 gene (brain-specific angiogenesis inhibitor) was related to higher anger expression-out (or an unmanageable tendency to manifest anger externally) in ADHD patients [41].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we also observed DNA methylation alterations of BAIAP2 and OXTR in sPTB cord blood, which were related to neurodevelopmental disorders. To specify, BAIAP2 encodes brain-specific angiogenesis inhibitor - binding protein that is involved in neurodevelopmental/ neurite outgrowth network [73], and its genotype and expression were associated with autism spectrum disorders (ASD) [74] and attention-deficit/hyperactivity disorder (ADHD) [73, 75, 76]. The methylation of the oxytocin receptor ( OXTR ) was also associated with ASD [25, 77].…”
Section: Discussionmentioning
confidence: 99%